CONTRIBUTION OF SELF-CONTROL AND CONFORMITY TO AGRESSION BEHAVIOR OF SMK BINA KARYA 1 KARAWANG STUDENTS - Muharsih, Lania; Uthomah, Laila; Solihin, Ismail (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the contribution of self-control and conformity to aggression behavior of SMK Bina Karya 1 Karawang students. The research methods use quantitative research methods with the type of correlational study. The subjects in this study is 274 male students, was taken using stratified random sampling technique. Method of collecting the data is using scale or questionnaire consisting of scale of self-control, conformity, and aggression behavior with Likert scale model. Data analysis techniques use simple correlation tests using the Pearson Product Moment correlation formula of double and multiple tests with the help of SPSS program version 24.00 for Windows. The results of the study using double correlation test show that between self-control and conformity with the aggression behavior acquired fcalculate value of 28 833 > Ftabel 3:02 with significance value of 0.000 > 0.05 which means there are significant relationship between self-control and conformity with aggression behavior. This analysis shows the value of the coefficient of determinant (R square) of 0175 meaning the magnitude of the contribution given by the variables of self-control and conformity to aggression behavior is 17.5%, while the remainder of 82.5% is contributed by other factors not examined in this study.